Contemporary Conflicts in Perspectives on Work Hours across Hierarchical Levels in Public Accounting - Baudot, Lisa; Kelly, Khim; McCullough, Aaron (The Accounting Review, 2022)
ABSTRACT Socializing personnel into accepting work hour norms has been fundamental to how accounting firms function, but is now challenged by contemporary work perspectives. Using 40 semi-structured interviews of personnel across hierarchical levels at a national firm and an international firm, we show how strangeness and contradiction expressed in work hour perspectives across different levels within both firms are reconstructed as compatible and complementary. Highlighting various firm adaptations, including alternative work arrangements, offshoring, and technological tools, our interviews suggest a major shift in firms' approach toward work hours. This shift is fueled by work perspectives embraced by younger generations desiring work-life balance and purposeful work, and enabled by technology supporting remote work and increasing work efficiencies. The question remains whether firms are evolving to genuinely embody work perspectives of younger generations or restructuring to rely on a smaller workforce willing to accept traditional work hour norms, or some combination thereof.